Mathematical Analysis Of Improving The Use And Creation Of Didactic And Exhibition Tools In Biology Teaching - Rozmatova Sharofat Tashmatjonovna; Boltayeva Muhayyo Dilshod kizi (Zien Journals, 2024)
Improving the methodology of using didactic-visual tools in the process of teaching biology is one of the current issues.Despite the fact that didactic materials are actively used by teachers in practice, they often use didactic materials mainly to monitor students' knowledge
Keywords: saw; I heard; I did; didactic-kdemonstrativethinking